2013
DOI: 10.1149/2.008402jss
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ce Concentration and Temperature on Photoluminescence Intensity in KCl:Ce3+Blue Phosphor

Abstract: Ce3+ ion is an important activator for various phosphors, but no detailed study has been performed on KCl:Ce3+. A Ce3+-doped KCl blue phosphor is synthesized from an aqueous solution of KCl − CeCl3. The structural and optical properties of the KCl:Ce3+ phosphor are investigated by X-ray diffraction (XRD) analysis, photoluminescence (PL) analysis, PL excitation spectroscopy, diffuse reflectance spectroscopy, and luminescence decay measurement. The XRD data indicate that the KCl host lattice can be expanded when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…The decay time of the KCl:Ce 3+ crystal grown in the present study has been obtained to be a constant of 35.14 ± 0.17 ns, which is slightly different from that reported (30 ns) for the KCl:Ce 3+ phosphors by Tosaka et al. [ 23 ] This decay time divergence can be attributed to the Ce‐doping concentration: Higher in KCl:Ce 3+ phosphor (0.01) [ 23 ] than in KCl:Ce 3+ crystal (0.006) (present study), causing the distance between Ce ions to be greater than or equal to the critical distance at which concentration quenching would occur. Moreover, it can be understood that the XRD, PL, and TL studies made in the present study have confirmed the trivalent state of Ce 3+ ion in the KCl host lattice.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The decay time of the KCl:Ce 3+ crystal grown in the present study has been obtained to be a constant of 35.14 ± 0.17 ns, which is slightly different from that reported (30 ns) for the KCl:Ce 3+ phosphors by Tosaka et al. [ 23 ] This decay time divergence can be attributed to the Ce‐doping concentration: Higher in KCl:Ce 3+ phosphor (0.01) [ 23 ] than in KCl:Ce 3+ crystal (0.006) (present study), causing the distance between Ce ions to be greater than or equal to the critical distance at which concentration quenching would occur. Moreover, it can be understood that the XRD, PL, and TL studies made in the present study have confirmed the trivalent state of Ce 3+ ion in the KCl host lattice.…”
Section: Resultscontrasting
confidence: 99%
“…Tosaka et al. [ 23 ] have discussed the effects of Ce concentration and temperature on photoluminescence (PL) intensity in KCl:Ce 3+ blue phosphor and found that the excitation and emission peaks of the Ce 3+ :4f↔5d transitions are strongly influenced by the Ce (doping) concentration, and suggest the use of the KCl:Ce 3+ phosphor in TL dosimetry. However, most of the work has been carried out in the form of powder or small size crystals.…”
Section: Introductionmentioning
confidence: 99%
“…25a shows our measured room-temperature PL decay curves for the Ce 3+ emission in (Ce 3+ , Mn 2+ )-codoped CaCO 3 phosphor 128 and that in KCl:Ce 3+ phosphor. 129 Figure 25b also shows the room-temperature PL decay curves for the Mn 2+ emission in (Ce 3+ , Mn 2+ )-codoped CaCO 3 phosphor 128 and that for the Mn 4+ emission in BaSiF 6 :Mn 4+ phosphor. 52 It should be noted that the 5d 1 → 4f 1 transitions in Ce 3+ are dipole allowed, whereas the intra-d-shell transitions in Mn 2+ and…”
Section: Oxide Hostmentioning
confidence: 99%
“…[32,33] It can be seen from the reflectance spectra that bands corresponding to 5d-configurations of Ce 3+ overlap with the CB and were observed at longer wavelengths, indicating a reduction in E g for the Ce-doped sample. [32,33] It can be seen from the reflectance spectra that bands corresponding to 5d-configurations of Ce 3+ overlap with the CB and were observed at longer wavelengths, indicating a reduction in E g for the Ce-doped sample.…”
Section: Band Gap Energies Of Undoped and Ce-doped Srbpo 5 By Drsmentioning
confidence: 99%
“…Doping of Ce 3+ at defined excited energy levels facilitated several distinct band transitions from the higher states, not found in the undoped sample. [32,33] The excitation peaks 262 and 315 nm peaks were assigned as 2 F 5/2 → 2 T 2 and 2 F 5/ 2 → 2 E transitions. Figure 4b shows the band gap energies estimated from the reflectance spectra of undoped and 0.1 mol% Ce-doped SrBPO 5 using the Kubelka-Munk (K-M) method.…”
Section: Band Gap Energies Of Undoped and Ce-doped Srbpo 5 By Drsmentioning
confidence: 99%